Is income inequality in Latin America falling? - Gasparini, Leonardo Carlos (2008)
This paper documents patterns and recent developments on income inequality in Latin America and the Caribbean (LAC). New comparative international evidence confirms that LAC is a region of high inequality, although maybe not the highest in the world. Income inequality has fallen in the 2000s, suggesting a turning point from the substantial increases of the 1980s and 1990s. The recent fall in inequality is significant and widespread, but it does not seem to be based on strong fundamentals.